Report of the first Vagococcus lutrae human infection, Marseille, France - V. Garcia; C. Abat; J.-M. Rolain (New Microbes and New Infections, 2016)
Vagococcus lutrae is a Gram-positive coccus initially isolated from the common otter (Lutra lutra) but that has never been reported as a human pathogen. We describe the first case of human infection due to Vagococcus lutrae in Marseille, France.